2022
DOI: 10.1177/01492063221117529
|View full text |Cite
|
Sign up to set email alerts
|

Good Soldiers Instead of Good Change Agents: Examining the Dual Effects of Self-Sacrificial Leadership on Pro-Social Behavior and Change-Oriented Behavior in Teams

Abstract: Previous research has predominantly regarded self-sacrificing leaders as role models that can drive desirable outcomes. We challenge this notion and demonstrate the dual effects of self-sacrificial leadership on team prosocial and change-oriented behaviors. Drawing upon social learning theory, we develop a nuanced model that simultaneously examines self-sacrificial leadership's beneficial effects on team helping and its detrimental effects on team change-oriented behavior via unique mechanisms. Our analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 150 publications
0
4
0
Order By: Relevance
“…Lee, Lyubovnikova [ 13 ] systematic review concludes that SL has the characteristics to satisfy subordinates based on emotional, ethical, spiritual, and relational grounds. According to Hoch, Bommer [ 40 ], the empirical power of SL is higher than other positive leadership styles, and it has emerged as one of the most important leadership styles for producing numerous positive outcomes including improving employees’ commitment [ 41 ], engagement [ 42 ], motivation and job performance [ 43 ], creativity and innovations [ 44 ], work-related wellbeing [ 45 ], innovative work behavior [ 46 ], citizenship behaviors [ 47 ], positive deviance [ 48 ], productive voice behavior [ 49 ] and pro-social behaviors [ 50 ].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Lee, Lyubovnikova [ 13 ] systematic review concludes that SL has the characteristics to satisfy subordinates based on emotional, ethical, spiritual, and relational grounds. According to Hoch, Bommer [ 40 ], the empirical power of SL is higher than other positive leadership styles, and it has emerged as one of the most important leadership styles for producing numerous positive outcomes including improving employees’ commitment [ 41 ], engagement [ 42 ], motivation and job performance [ 43 ], creativity and innovations [ 44 ], work-related wellbeing [ 45 ], innovative work behavior [ 46 ], citizenship behaviors [ 47 ], positive deviance [ 48 ], productive voice behavior [ 49 ] and pro-social behaviors [ 50 ].…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Self-sacrificial leaders have a strong sense of responsibility to ensure that they fulfill their obligations to the team and ultimately achieve the team's goals. Because of self-sacrificial leaders' dutiful practice of focusing on follower Workplace loneliness needs and collective goals, employees generally perceive them to be other-focused rather than self-focused; they trust such leaders to have their best interests at heart and, thus, do not fear being exploited (De Cremer and van Knippenberg, 2005;Liu and Xu, 2022). Self-sacrificial leadership is conceptually distinct from transformational leadership and humble leadership.…”
Section: 3mentioning
confidence: 99%
“…Although the above studies have confirmed that employees can have a positive response to a leader’s self-sacrifice behavior—that is, they can demonstrate good work results—these studies also reveal that scholars know little about the negative impact it may cause ( Liu et al, 2022 ). The present study argues that scholars pay too much attention to the positive impact of leadership self-sacrifice behavior while ignoring its possible negative impact and its potential double-edged sword effect.…”
Section: Introductionmentioning
confidence: 97%
“…Over the last two decades, scholars have extensively focused on the subject of leader self-sacrifice. Numerous researches have shown that leaders’ self-sacrifice behavior arouses positive emotions in employees ( De Cremer et al, 2009 ; Vianello et al, 2010 ), which improves helping behavior ( Liu et al, 2022 ), work engagement ( Mostafa and Bottomley, 2020 ) and task performance ( Jiang et al, 2019 ). In short, there seems to be a common consensus among scholars that employees can be encouraged by leaders’ self-sacrifice behavior to produce better work results.…”
Section: Introductionmentioning
confidence: 99%